دور التعليم في تنمية الموارد البشرية وأثره في الاقتصاد الوطني - صقر أديب (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تعد الموارد البشرية المحور الذي تدور حوله أي خطة في عملية النماء الشامل ، فهي الأساس في نجاح أي بناء اقتصادي لاسيما إن التخلف بحد ذاته لا يرتبط بالبلد أو الدولة بقدر ارتباطه بهذه الموارد والقوى العاملة منها ,على اعتبار إنها القوة القادرة على الأخذ بأسباب النمو والتطور والتجديد. وإذا كانت التنمية الاقتصادية والاجتماعية تطمح إلى تحقيق حياة أفضل ، فان الاهتمام بالموارد البشرية وتنميتها هو احد أهم الوسائل التي تكفل تحقيق هذا الهدف. ويتم إعداد وتهيئة هذه الموارد من خلال عملية التعليم الذي يتوقف عليها تطور عملية التنمية في أي بلد من البلدان . ولعل نقص الكوادر الفنية والإدارية المؤهلة والمتدربة هي المشكلة الأساسية التي تحد من مسيرة التقدم الاقتصادي والاجتماعي في بلدان العالم النامي. فبسبب هذه المشكلة لاتزال هذه البلدان تتعثر في عملية التنمية حتى تلك الدول التي تمتلك وفرة من رأس المال والموارد الطبيعية. يهدف هذا البحث إلى تسليط الضوء على دور التعليم في زيادة وتحسين إنتاجية العمل و أهمية الاستثمار في العنصر البشري ودوره في عملية التنمية . بالإضافة إلى الأهمية النسبية للعمالة في الدخل القومي مقارنةً بأهمية التكوين الرأسمالي . The human resources are the basic center for any plan in the process of a comprehensive development in addition to this the human resources play a Kay role in success of any economic establishment. The relationship between retardation and human resources is retardation and any city or country, due to the fact that human resources have a notable ability in achievement of growth and renewal . If the social and economic development aims to accomplish awe fare life, then because these two actions are the most important to realize this goal. These resources are prepared through the process of education which has a Kay part in development process in any country . Maybe the lack of skilled and qualified technical and administrative staff is the major problem that restricts the economic and social progress in any underdeveloped countries. Because of this problem, these countries meet with difficulties in development process. Even the countries which have abundance of capitals and natural resources face the same problem. This search has studied the role of education in increasing and improvement the worker production and the importance of human beings investment and its role in the process of development .In addition the relative importance of the workers in national income in comparison with the importance of capitalist formation .